Promoting Physical Activity among Buddhist Monks: The Role of Nurse - Laochai, Wiwat; Thummakul, Doungnetre; Jiraprapapong, Nongluck (Journal of Food Health and Bioenvironmental Science, 2023)
Buddhist monks suffer from chronic illnesses that could be prevented or delayed if they engaged in proper physical activity. Because a monk’s lifestyle differs from a normal Buddhist, physical activity maybe neglected. Physical activity is usage of energy by using muscles in various parts of the body. If the body does not completely metabolize excess fat, it will result in accumulation of fat. Nurses have an important role in promoting physical activity among Buddhist monks, which will result in better health for monks, prevention of complications of diseases and reduce risk of noncommunicable diseases (NCDs) such as diabetes, hypertension, chronic kidney disease, hyperlipidemia, obesity, heart disease, cancer and osteoporosis, which is usually caused by monks’ lack of physical activity. Buddhist monks have religious disciplines and duties that make their life style differ from normal citizens. This article shows the role of nurses in promoting physical activity among Buddhist monks that doesn’t go against monks’ discipline; consisting of evaluation of physical activity using Global physical activity questionnaire, International physical activity questionnaire, calculation of energy usage (Metabolic Equivalent: MET), different ways for monks to exercise such as fast walking, Taichi-Qigong, Yoga and concentration activity, including the spread of awareness to monks and nurses to support and design physical activity program that is adequate and suitable for monks. If nurses become more active and emphasize this topic more, there will be more projects and programs that promotes physical activities among monks to improve monks’ physical well-being.